The Reduced Recombination and the Enhanced Lifetime of Excited Electron in QDSSCs Based on Different ZnS and SiO2 Passivation - Ha Thanh Tung; Nguyen Thu Thao; Lam Quang Vinh (International Journal of Photoenergy)
In this study, we focus on the enhanced absorption and reduced recombination of quantum dot solar cells based on photoanodes which were coated by different ZnS or SiO2 passivations using the successive ionic layer absorption and reaction methods. The quantum dot solar cells based on photoanode multilayers, which were coated with a ZnS or SiO2 passivation, increased dramatic absorption in the visible light region as compared with other photoanodes and reduced rapid recombination proccesses in photovoltaic. As a result, the performance efficiency of TiO2/CdS/CdSe photoanode with SiO2 passivation increased by 150% and 375% compared with TiO2/CdS/CdSe with ZnS passivation and TiO2/CdSe photoanode, respectively. For this reason, we note that the tandem multilayers can absorb more wavelengths in the visible light region to increase a large amount of excited electrons, which are transferred into the TiO2 conduction band, and decrease number of electrons returned to the polysulfide electrolyte from QDs when a ZnS or SiO2 passivation is consumed. Moreover, it is obvious that there was a far shift towards long waves in UV-Vis spectra and a sharp drop of intensity in photoluminescence spectra. In addition, the dynamic process in solar cells was carried out by electrochemical impedance spectra.